A study on high-viscosity oil-water two-phase flow in horizontal pipes - Shi, Jing (Cranfield University, 2015)
A study on high-viscosity oil-water flow in horizontal pipes has been conducted applying experimental, mechanism analysis and empirical modelling, and CFD simulation approaches. A horizontal 1 inch flow loop was modified by adding a designed sampling section to achieve water holdup measurement. Experiments on high-viscosity oil-water flow were conducted. Apart from the data obtained in the present experiments, raw data from previous experiments conducted in the same research group was collated. From the experimental investigation, it is found that that the relationship between the water holdup of water-lubricated flow and input water volume fraction is closely related to the oil core concentricity and oil fouling on the pipe wall. The water holdup is higher than the input water volume fraction only when the oil core is about concentric. The pressure gradient of water-lubricated flow can be one to two orders of magnitude higher than that of single water flow. This increased frictional loss is closely related to oil fouling on the pipe wall. Mechanism analysis and empirical modelling of oil-water flow were conducted. The ratio of the gravitational force to viscous force was proposed to characterise liquid-liquid flows in horizontal pipes into gravitational force dominant, viscous force dominant and gravitational force and viscous force comparable flow featured with different basic flow regimes. For viscous force dominant flow, an empirical criterion on the formation of stable water-lubricated flow was proposed. Existing empirical and mechanistic models for the prediction of water holdup and/or pressure gradient were evaluated with the experimental data; the applicability of different models is demonstrated. Three-dimensional CFD modelling of oil-water flow was performed using the commercial CFD code Fluent. The phase configurations calculated from the CFD model show a fair agreement with those from experiments and mechanism analysis. The velocity distribution of core annular flow is characterised with nearly constant velocity across the oil core when the oil viscosity is significantly higher than the water viscosity, indicating that the high-viscosity oil core flows inside the water as a solid body. The velocity profile becomes similar to that of single phase flow as the oil viscosity becomes close to the water viscosity.
Keywords: Oil-water; High-viscosity oil; Water holdup; Oil fouling; Pressure gradient; CFD